PENGARUH PENGGUNAAN TEPUNG Lemna sp. TERFERMENTASI PADA PAKAN BUATAN TERHADAP TINGKAT PEMANFAATAN PAKAN, PERTUMBUHAN DAN KELULUSHIDUPAN BENIH IKAN LELE DUMBO (Clarias gariepinus) - Ika Nurul Asriyanti; Johannes Hutabarat; Vivi Endar Herawati (University of Lampung, 2018)
The cost of feed is one of the production costs that account for 65%, so the need for alternative feed ingredients that can reduce feed costs. Lemna plant has good enough nutrition as alternative food such as protein 32,13%, nitrogen extract (BETN) 15,96%, and fat 5,13%, crude fiber 28,58% and ash 18, 20% that can be used as fish feed ingredients.The aim of this study is to determine the effect and the best dose level of fermented lemna flour to the level of feed utilization, growth and survival of dumbo catfish (C. gariepinus).The experimental fish used was juvenile of catfishwith an average individual body weight of 3,43±0,06 g and the density of 1 fish/2 l for 42 days. This experimental applied completely randomized design (CRD), which consisted of 5 treatments and 3 replicates. The treatments were treatment each by an addition of flour lemna fermented 0% (A), 5% (B), 10% (C), 15% (D) and 20% (E) respectively. The results showed that the flour lemna fermented provided significantly effect (P<0,05) on total feed comsumption, feed utilization effeciency), protein efficiency ratio and relative growth rate. However, no significant effects (P>0,05) wereoccured on the values of survival rate. The highest dose of 20% dose of fermented lemon flour resulted in total feed intake of 170.01 ± 9.25 g, feed efficiency of 78.82 ± 4.75%, protein efficiency ratio of 2.49 ± 0.15% and the relative growth rate (of 4.60 ± 0.31% / day, while the optimum dose of fermented lemon flour to total feed consumption, the efficiency of feed utilization protein efficiency ratio and relative growth rate have not found the optimum point because based on orthogonal polynomial test still patterned linear.